Medium and Large Vector-Based SVPWM Technique for Five-Phase Two-Level Inverter - Deniz, Erkan (My University, 2021)
In recent years, interest in the use of multi-phase (more than three-phase) dc/ac inverters in applications such as electric vehicles, electric traction, more electric aircraft, ship propulsion, aerospace applications, etc. has been increasing day by day. The paper presents the Discontinuous Space Vector Pulse Width Modulation (DSVPWM) technique for control of a five-phase two-level inverter. The five-phase DSVPWM algorithm uses zero, medium and large vectors combination. When calculating vectors dwell times, calculations are made by directing the Vref to Sector-1 regardless of which sector it falls into. Thus, complex calculations are reduced. DSVPWM controlled five-phase two-level inverter that feeds an RL load is simulated using MATLAB/Simulink-Simscape blocks. To demonstrate the effectiveness of the used DSVPWM algorithm, five-phase inverter's output voltages, current waveforms and their FFT analysis are given for different modulation indexes and switching frequencies.
Keywords: Discontinuous Space Vector PWM Five Phase Inverter Large and Medium Vectors THD Analysis